A free accessible individual-based simulator enabling virtual experiments on soil organic matter processes in classroom - Anna Gras; Juan Carlos Cañadas; Marta Ginovart (OmniaScience, 2013)
This work addresses and aims to fulfil a very clear need in teaching biosystem engineering. When introducing students to the complexity of soil processes, one of the frustrations that teachers often experience is the impossibility to demonstrate practically, in the lab, some of the concepts and processes discussed in class. Either the experiments take far longer than a typical laboratory session or they require access to specific equipment. To deal with this situation, it would be ideal for students to be able to do virtual experiments. The purpose of this work is to display the individual-based simulation model INDISIM-SOM, available free from a website, and to show how it can be used in experiments or as a teaching-learning instrument in the classroom. The computational model has been designed specifically for the study of soil organic matter and is based mainly on the activity conducted by two different prototypes of microorganisms. One option of using INDISIM-SOM is as a way to introduce the individual-based model as a methodology to improve understanding of the agents involved in soil microbial system and their processes. Another option is to develop the ability to work with simulators by connecting concepts and helping students in the development of modelling competence. Virtual experiments were carried out as an example of what may be expected from using the INDISIM-SOM web simulator. Temporal evolutions of five virtual soils with different organic C content and proportional content in organic N, easily hidrolyzable N, nitrate and ammonia were generated and discussed.